MODEL PEMBELAJARAN VARIATIF (MPV) YANG MEMBERDAYAKAN MULTIPLE INTELLIGENCE AUD DALAM BELAJAR BAHASA INGGRIS - Suratmi, Nanik (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2011)
This study is done in order to know the implementation of MPV for developing multipleintelligence AUD and returning to the true function of Kindergarten as a beautiful place forlearning by playing. The design used is action research based on naturalistic-qualitative. Theinstruments used are the researcher as the main instrument, observation, and photographs.The result of data analysis showed that are not only the two hypotheses are accepted but alsothe four research problems are solved